Squaraine-linked metalloporphyrin two-dimensional polymer photocatalyst for hydrogen and oxygen evolution reactions - Ranjeesh, K. C.; George, L.; Wakchaure, V. C.; Goudappagouda; Devi, R. N.; Babu, S. S. (Chemical Communications, 2019)
Efficient water splitting photocatalysts are an energetically demanding and cost-effective method for generating renewable energy. Significant research has been reported to advance this approach. However, the use of organic photocatalysts and the presence of residual catalysts trapped in the porous frameworks present major concerns about the efficiency of this strategy. Herein, we report the photocatalytic evolution of H2 and O2 by a multi-hydroxyl group-decorated metalloporphyrin-based two-dimensional catalyst developed via metal catalyst-free synthetic route. Though metalloporphyrins have long been used for catalytic functions, a heterogeneous photocatalyst delivering both H2 and O2 has not yet been realized. This polymer catalyst design enables the photocatalytic diatomic O2 release, a bottleneck in water splitting, in a facile way. Photocatalytic release of H2 as well as O2 occurs with long-term durability of 20 cycles in 300 days with negligible decrease in efficiency, thus demonstrating the excellent performance of this new catalyst.